Interpersonal Metafunction Analysis of Smartphone Slogans - Sumari, Binti Aisiah Daning (International Journal of English Education and Linguistics (IJoEEL), 2024)
This study presents an interpersonal metafunction analysis of smartphone slogans. Since the smartphone has been extensively commercialized, companies create different slogans for every single edition. Though it is usually formulated in short-purposive phrases and does not straightforwardly magnetize purchasers, the slogan is a form of language to support a market campaign. Slogans are usually embodied in clauses or sentences; part of grammar; a “system of wordings” (Matthiessen and Halliday: 1997). The Systemic Functional Linguistics (SFL) approach was conducted to scrutinize the realization of the lexicogrammar level revealed through MOOD’s interpersonal meaning. By using the descriptive qualitative method, SFL, and UAM CorpusTool,  it was found that the realization of MOOD in this study shown in percentage; declarative clause 6,4% or N=51; interrogative clause 0,1% or N=1; and imperative clause 3,4% or N=27. This result, it shows that the declarative clause is the most frequently used in creating smartphone slogans, to provide information and offering products at once. It can be concluded that from selected smartphone slogans, predominantly, companies shows that they have a wider knowledge of the products through delivering, informing, offering, demanding, and commanding customers. Ergo, success in acknowledging their prospective customers about their products’ eminence will attract customers.